2014
DOI: 10.1177/0025802414532247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the hospitalisation of mentally ill offenders in the Forensic Unit of the Clinic of Psychiatry in Pristina over a three-year period and long-term strategy implications for the management of the Forensic Mental Health System Service

Abstract: Rehabilitation programmes for treatment and management are needed that specifically focus on psychotic disorders, severe personality disorders and drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The first concerns criminally responsible offenders that receive the requisite psychiatric treatment via psychiatric consultations on a voluntary basis [ 3 – 5 ]. When needed, inpatient mental health care for this population may be provided via voluntary or compulsory admission to psychiatric hospitals [ 6 , 7 ] or, more rarely, in prison psychiatric wards [ 8 ]. The second refers to offenders with decreased responsibility or high risk of recidivism due to long-lasting mental disorders identified via psychiatric expert witness.…”
Section: Introductionmentioning
confidence: 99%
“…The first concerns criminally responsible offenders that receive the requisite psychiatric treatment via psychiatric consultations on a voluntary basis [ 3 – 5 ]. When needed, inpatient mental health care for this population may be provided via voluntary or compulsory admission to psychiatric hospitals [ 6 , 7 ] or, more rarely, in prison psychiatric wards [ 8 ]. The second refers to offenders with decreased responsibility or high risk of recidivism due to long-lasting mental disorders identified via psychiatric expert witness.…”
Section: Introductionmentioning
confidence: 99%
“…However, forensic psychiatric services and the facilities in which they are provided are defined and governed in different ways across the world: some countries have issued detailed criteria for different levels of secure care, including building design and material specifications [ 4 – 6 ], whereas in other countries, security is much more loosely defined, and has essentially developed over time along with clinical practices [ 7 – 9 ]. This is mainly due to variation in the specifics of legislation and the particular ways in which forensic mental health systems are operationalized in different countries, as the underlying clinical issues and principles remain relatively similar across countries [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 In a study from South India, schizophrenia and other psychotic disorders made up 28.9% of diagnoses. 20 Ibishi et al reported that 69.1% of mentally ill offenders had a psychotic disorder, 21 whilst Fioretti et al found a prevalence of 65.6% for schizophrenia. 19 These studies and our study support the notion that those who are likely to commit violent crimes within the psychiatric population are those diagnosed with psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%